Crystal structure of N,N,N',N'-tetramethylethylenediammonium dinitrate - Donia, Zaouali Zgolli; Boughzala, Hbib; Driss, Ahmed (European Journal of Chemistry, 2011)
N,N,N',N'-tetramethylethylenediammonium dinitrate has been synthesized. The crystal and molecular structure of the title compound has been determined from single crystal X-ray diffraction data. C6H18N4O6, M =242.24, Triclinic, a = 6.040(2) Å, b = 6.834(3) Å, c = 7.867(2) Å, α = 74.1120(10)°, β = 83.700(2)°, γ = 80.314(2)°, V = 307.12(19) Å3, T = 298(2) K, space group P-1 (no. 2), Z = 1, μ(Mo-Kα) = 0.115, 2383 reflections measured, 1342 unique (Rint = 0.0169) which were used in all calculations. The final wR(F2) was 0.1262 (all data). In the title compound, C6H18N22+.2NO3-, both N atoms of the cationic moiety are protonated and linked via hydrogen bonds to two trigonal planar nitrate anions. Two types of classical hydrogen bonds are observed: N1-H…O1 and N1-H…O2. These bonds link the cations and the anions together, forming a one-dimensional network and reinforcing the cohesion of the ionic structure.